Estudo do consumo de linha de costura em confecção de moda underwear - Imbriani, Thaina Rodrigues (2023)
One of the main parameters related to good efficiency and cost reduction in an industry is the estimated consumption of its inputs. Sewing threads are considered an extremely important raw material in clothing, and it is necessary to estimate their consumption for better planning and control of production, avoiding waste or shortages during the production of a collection. Currently, existing theoretical methods are inaccessible to the reality present in industries, leading to the search for more accessible methods. The present work aimed to propose a method for determining sewing thread consumption in a fashion underwear manufacturing industry, through the quantity of sewing thread cones used in each sewing machine in conjunction with the method of thread consumption per sewing meter, the data were obtained in the company studied through observation, unstructured interviews, creation of a database and assistance from existing theoretical methods for this topic. The results obtained demonstrated that the determination of sewing thread consumption using the method adopted in the present work proved to be efficient and assertive considering the reality of the company studied.